Hostel Residents' Knowledge on Feminine Hygiene—Effect of Information Booklet - Alva, Jeevitha; Kannappan, Sujatha R.; Joseph, Gincy; Upashe, Shivaleela (Journal of Health and Allied Sciences NU, 2021)
Purpose of the Study Adolescence is the transformational period of life from childhood to adulthood. Pubertal changes influence the functioning of the reproductory tract of adolescent girls. At this stage, adequate knowledge of feminine hygiene becomes vital in the prevention of urinary tract infection; if not treated, it may cause various complications in the future. Hence, every adolescent girl needs to be educated on the importance of maintaining femininity.Methods A quantitative research methodology was adopted, with a one-group pre- and posttest design. A random sampling procedure was used to find 100 samples that met the inclusion criteria. A structured knowledge questionnaire was used to get the essential data. Following the pretest, an information brochure on feminine hygiene was distributed. After 7 days, a posttest was conducted.Results The acquired data were analyzed with descriptive and inferential statistics. Around 72% of the participants were under the age of 18. Thirty percent of them did not receive any feminine hygiene information. The mean posttest knowledge score of 16.54 is higher than the pretest knowledge score of 14.31, indicating that understanding of feminine hygiene has improved.Conclusion In the pretest, 39% of hostel residents had poor awareness of feminine hygiene, indicating a need for instruction. The difference in knowledge score between pre- and posttest knowledge demonstrates the usefulness of the information booklet in enhancing feminine hygiene knowledge.
Keywords: adolescent; female; hygiene; infection; pamphlets